Trends in COVID-19 vaccination intent from pre- to post-COVID-19 vaccine distribution and their associations with the 5C psychological antecedents of vaccination by sex and age in Japan. Issue 11 (2nd November 2021) - Machida, Masaki; Nakamura, Itaru; Kojima, Takako; Saito, Reiko; Nakaya, Tomoki; Hanibuchi, Tomoya; Takamiya, Tomoko; Odagiri, Yuko; Fukushima, Noritoshi; Kikuchi, Hiroyuki; Amagasa, Shiho; Watanabe, Hidehiro; et al.
ABSTRACT: Vaccine hesitancy regarding the coronavirus disease 2019 (COVID-19) vaccine is widespread during the COVID-19 pandemic. Many recent studies have reported that the confidence of the vaccination and perceived risk were associated with vaccination intent, yet few studies have focused on other psychological factors. This study aimed to clarify the trends in COVID-19 vaccination intent and to identify the association between the 5C psychological antecedents and COVID-19 vaccination intent by sex and age in Japan. This was a longitudinal study conducted through an Internet-based survey from January 2021 to April 2021 before and after vaccine distribution in Japan, including 2, 655 participants recruited by quota sampling. Participants were asked to indicate how likely they were to get vaccinated against COVID-19. In the second survey, the participants responded to questions regarding the 5C psychological antecedents: confidence, complacency, constraints (structural and psychological barriers), calculation (engagement in extensive information searching), and collective responsibility (willingness to protect others). Multiple logistic regression analysis was performed to clarify the association between the 5C psychological antecedents and COVID-19 vaccination intent in the second wave survey. COVID-19 vaccination intent improved from 62.1% to 72.4% after vaccine distribution, but no significant difference was found in young men. Confidence and collective responsibility were positively associated with vaccination intent, and calculation was negatively associated among all generations. COVID-19 vaccination intent may be affected not only by confidence and constraints but also by calculation and collective responsibility, and further research is needed.